Will autonomous vehicles change auto commuters' value of travel time?. (June 2020) - Zhong, Haotian; Li, Wei; Burris, Mark W.; Talebpour, Alireza; Sinha, Kumares C.
Highlights: Autonomous vehicles could reduce commuters' value of travel time by 18–32% (8–14% for shared autonomous vehicles) compared to driving. The reductions are largest for suburban communters, followed by their urban and rural counterparts. Such an impact is not significant for commuters who are currently passengers while commuting. Abstract: This paper examines the potential impact of autonomous vehicles on commuters' value of travel time (VOTT). In particular, we focus on the effect on auto commuters in small and medium-sized metropolitan areas, concerning the spatial variability across urban areas, suburbs, and rural areas. We design a stated choice experiment to elicit potential changes in 1, 881 auto commuters' valuation of travel time in autonomous vehicles and apply a mixed logit model to quantify the changes in the value of travel time if taking autonomous vehicles. The results of this study suggest that the effect of autonomous vehicles on the VOTT is spatially differentiated. We find that riding in a private autonomous vehicle reduces the commuting VOTT of suburban, urban, and rural drivers by 32%, 24%, and 18%, respectively, compared to 14%, 13%, and 8% for riding in a shared autonomous vehicle. Finally, we discuss the implications of these lower values of time on transportation and land use planning.